STRUCTURAL CHARACTERISTICS OF NATURAL EVERGREEN FORESTS IN EASTERN REGION OF THAILAND - Glumphabutr, Parinya; Kaitpraneet, San (วารสารวนศาสตร์ไทย, 2022)
The structural characteristics of natural evergreen forests in eastern region of Thailand was studied in moist evergreen forest (MEF), hill evergreen forest (HEF) at Khao Khitchakut National Park, and in dry evergreen forest (DEF) at Khao Soi Dao Wildlife Sanctuary, Chanthaburi province during November 1999 to December 2000. The results revealed that the species numbers of trees with DBH larger than 4.5 cm. of MEF, DEF, and HEF are 135, 138, and 129 species/ha. DEF is found to have maximum species diversity while the minimum is recorded for HEF. Stand densities of MEF, DEF, and HEF are 1,510; 1,355 and 2,513 trees.ha-1, respectively with the basal areas of 0.4799, 0.3995 and 0.3161 %, respectively. Scaphium macropodum Beaumee is found to have the highest importance value index in MEF, while Diospyros dictyoneura Hiern in DEF and Castanopsis acuminatissima Rehd in HEF. The vertical arrangements in MEF and DEF are divided into 4 layers while HEF has only 3 layers. The crown covers of MEF, DEF, and HEF are 83.05, 89.05 and 81.52 %, respectively.